2013
DOI: 10.1002/adsc.201200732
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Recyclable Catalyst for N‐Alkylation of Amines and β‐Alkylation of Secondary Alcohols with Primary Alcohols: SBA‐15 Supported N‐Heterocyclic Carbene Iridium Complex

Abstract: A mesoporous silica (SBA-15)-supported pyrimidine-substituted N-heterocyclic carbene iridium complex was prepared and used as a catalyst for both environmentally friendly N-alkylation of amines and b-alkylation of secondary alcohols with primary alcohols. The structure of the supported iridium catalyst was characterized by Fourier transform infrared (FT-IR), 13 C and 29 Si solid-state nuclear magnetic resonance (NMR), small-angle X-ray scattering (SAXS), transmission electron microscopy (TEM), iridium K-edge X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 63 publications
0
42
0
2
Order By: Relevance
“…AS BA-15-supported Ir/NHC complex was also reported as the catalyst for b-alkylation of secondary alcohols with primary alcohols. [87] AP t/q-Al 2 O 3 catalyst efficiently promoted the 3-alkylation of indoles [Eq. (27)].…”
Section: Heterogeneous Transition-metal-catalyzed C-alkylation Of Ketmentioning
confidence: 99%
“…AS BA-15-supported Ir/NHC complex was also reported as the catalyst for b-alkylation of secondary alcohols with primary alcohols. [87] AP t/q-Al 2 O 3 catalyst efficiently promoted the 3-alkylation of indoles [Eq. (27)].…”
Section: Heterogeneous Transition-metal-catalyzed C-alkylation Of Ketmentioning
confidence: 99%
“…The fermentation mixture of the IBE conversion also did not lead to C 5 product formation. The condensation of secondary alcohols with primary alcohols thus effectively catalysed by homogeneous base and homogeneous/heterogeneous transition metal systems [9,27,28] but never a pure heterogeneous catalytic system.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of ethanol into n-butanol over purely heterogeneous catalysts has been reported in several publications and patents [8][9][10][11][12][13][14][15][16][17][18]. Generally, the reaction temperature varies from 200 up to 450 • C with a relatively low conversion (e.g., 10%-20%) and a selectivity approaching 70%.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, successful examples of highly active coupling of aryl chlorides with arylboronic acids were rare [41]. Based on our previous work [42][43][44][45][46][47], we designed four immobilized catalysts with different Pd-NHC moieties using SBA-15 as support. Our result demonstrated that both catalytic activities and recycling performance were improved through adjusting the tethering strategy of ligands to supports.…”
Section: Introductionmentioning
confidence: 99%